2010
DOI: 10.1177/009164711003800303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Impact of Transition Seminars on Missionary Kids’ Depression, Anxiety, Stress, and Well-Being

Abstract: Missionary Kids (MKs) are included in a broader population defined as Third Culture Kids (TCKs), children who are raised outside of their parents’ home cultures (Pollock & Van Reken, 2001). This upbringing affords positive opportunities to experience diverse cultures but may also contribute to identity struggles and feelings of cultural isolation (Gillies, 1998; Hill, 2006; Pollock, 1989). To facilitate successful transitions from living overseas to the US, several reentry programs have been developed, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…In addition, the literature generally shows that individuals who moved to another culture at a younger age have more difficulty readjusting to their heritage culture [ 5 , 23 , 40 ]. At re-entry, younger sojourners reported feeling as if they “did not fit in” ([ 3 ]; p. 217), higher levels of depression and social difficulty [ 23 ], lower emotional stability [ 41 ], and elevated levels of anxiety, depression and stress alongside lower general psychological well-being [ 42 ]. Cox [ 23 ] suggested that younger sojourners had an advantage in learning the new culture during expatriation, which in turn made it more difficult to adapt during repatriation.…”
Section: Third Culture Individualsmentioning
confidence: 99%
“…In addition, the literature generally shows that individuals who moved to another culture at a younger age have more difficulty readjusting to their heritage culture [ 5 , 23 , 40 ]. At re-entry, younger sojourners reported feeling as if they “did not fit in” ([ 3 ]; p. 217), higher levels of depression and social difficulty [ 23 ], lower emotional stability [ 41 ], and elevated levels of anxiety, depression and stress alongside lower general psychological well-being [ 42 ]. Cox [ 23 ] suggested that younger sojourners had an advantage in learning the new culture during expatriation, which in turn made it more difficult to adapt during repatriation.…”
Section: Third Culture Individualsmentioning
confidence: 99%
“…When assistance with reentry issues exceeds the array of services available by the career services practitioner, referral for personal counseling or specific services may be warranted. MK transition seminars have been shown to be effective in reducing depression, anxiety, and stress, as well as improving overall psychological well‐being for repatriating MKs (Davis et al, ). In parallel, future MK career development research should also include variables (e.g., covariates) that assess the level of sociocultural adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Cockburn () suggested that TCKs (especially those with special needs) are vulnerable to risks related to frequent school change. The MK college transition represents another in a series of geographic transitions (Choi, ; Cockburn, ; Edwards & Steinglass, ; Hervey, ), requires an international separation from parents (Choi, ), and requires sociocultural adaptation to the United States (Bikos et al, ; Davis et al, ).…”
Section: Challenges Associated With Mk Repatriationmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in a study by Davis, Suarez, Crawford, and Rehfuss (2013), the researchers investigated the effectiveness of a 13-day reentry program that was designed to facilitate easier transitions from the host culture to the home culture. Modeling the exploratory study by Davis et al (2010), the seminar included individual counseling, group discussions, and social activities. The results demonstrated that MKs had a significant decrease in levels of depression, anxiety, and stress following the seminar.…”
mentioning
confidence: 99%